THE IMPACT OF TECHNOSTRESS AND ORGANIZATIONAL SUPPORT ON EMPLOYEE WELL BEING: EXAMINING BURNOUT AS A MEDIATOR - Nasra; Irsan Tricahyadinata; Saida Zainurossalamia ZA (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study analyzes the influence of technostress and organizational support on employee well-being, with burnout as a mediating mechanism in public sector digital bureaucracy. Digital transformation in local government performance systems creates technological demands that can drain employees' psychological resources. Based on the integration of JD-R theory and Perceived Organizational Support theory, this quantitative study used an SEM PLS approach on 57 employees. The results show that technostress directly increases burnout and decreases well-being, whereas organizational support effectively suppresses burnout but does not have a significant direct effect on well-being. Burnout decreases well-being but does not significantly mediate all tested relationships. These findings extend the theory by showing that in the context of a control-oriented digital bureaucracy, technological stress can directly decrease well-being without the accumulation of chronic fatigue. The theoretical and policy implications emphasize the importance of adaptive and resource-oriented digital design.